Between International Relations and Arms Controls: Understanding Export Controls for Surveillance Technologies - Wagner, Ben; Bronowicka, Joanna (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2015)
Export Controls are becoming an increasingly important dimension of international relations, however there is still relatively little literature on their usage and implementation. The following article attempts to show the development and problems surrounding export controls in a new area: surveillance technologies. These have recently been integrated into international frameworks for export controls, bringing with them a row of challenges and questions for policy makers. Based on extensive conversations with practitioners and key experts in the field, this paper attempts to sketch out key ideas and solutions in this area as well as important responses that have been developed to (perceived) challenges.

Kontrole eksportu stają się coraz ważniejszym wymiarem stosunków międzynarodowych. Stale jest jeszcze jednak stosunkowo mało literatury na temat ich wykorzystania i wdrażania. Niniejszy artykuł jest próbą ukazania rozwoju i problemów związanych z kontrolą eksportu w nowym obszarze: technologiach nadzoru, które niedawno zostały włączone do struktur międzynarodowych w zakresie kontroli eksportu, przynosząc ze sobą szereg wyzwań i pytań dla decydentów. Na podstawie przeprowadzonych rozmów z praktykami i kluczowymi ekspertami w tej dziedzinie autorzy artykułu próbują nakreślić najważniejsze pomysły i rozwiązania w tym obszarze, jak również istotne odpowiedzi, które zostały opracowane w kontekście (dostrzegalnych) wyzwań.
Kontrola eksportu technologii nadzoru w ujęciu pomiędzy stosunkami międzynarodowymi a kontrolą zbrojeń
Keywords: export controls; surveillance technology; international relations; global governance; kontrola eksportu; technologia nadzoru; stosunki międzynarodowe; global governance